FRI0286 IXEKIZUMAB TREATMENT IMPROVES FATIGUE, SPINAL PAIN, STIFFNESS, AND SLEEP IN PATIENTS WITH NON-RADIOGRAPHIC AXIAL SPONDYLOARTHRITIS. (2nd June 2020) - Mease, P. J.; Deodhar, A.; Rahman, P.; Marzo-Ortega, H.; Strand, V.; Hunter, T.; Adams, D.; Sandoval, D.; Kronbergs, A.; Zhu, B.; Leung, A.; Liu Leage, S.; et al.
Abstract : Background: Common symptoms of axial spondyloarthritis (axSpA) include fatigue, spinal pain, stiffness, and sleep problems, which can impair health-related quality of life. Ixekizumab (IXE) treatment shows efficacy in active non-radiographic axSpA (nr-axSpA). 1 Objectives: To assess fatigue, spinal pain, stiffness, and sleep with IXE treatment versus (vs) placebo (PBO) in patients (pts) with active nr-axSpA up to 16 and 52 weeks (wks). Methods: In COAST-X, pts with active nr-axSpA were randomized to 52 wks of double-blind IXE 80 mg once every 4 wks (Q4W) or 2 wks (Q2W), or PBO. Data were collected from baseline to Wk 52. Results: At Wk 16, IXE Q4W significantly improved fatigue, spinal pain, and stiffness, and IXE Q2W improved spinal pain, spinal pain at night, and stiffness vs PBO (Table). At Wk 52, IXE Q4W significantly improved stiffness, and IXE Q2W improved spinal pain, spinal pain at night, and stiffness vs PBO. Numeric improvements in sleep were not significant vs PBO. Wk 1, and up to Wk 16, IXE Q4W and Q2W significantly reduced spinal pain and stiffness vs PBO; stiffness was significantly reduced vs PBO up to Wk 52 (Figure). Conclusion: IXE Q4W and/or Q2W significantly improved spinal pain, spinal pain at night, and stiffness vs PBO at 16 and 52 wks in pts with nr-axSpA. IXE Q4W also improved fatigue at 16 wks in these pts. Numerical improvements in sleep were not significant vs PBO. References: [1]Deodhar A, et al. Lancet. 2019 Disclosure of Interests: Philip J Mease Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Janssen, Eli Lilly, Novartis, Pfizer, Sun Pharma, UCB Pharma, Consultant of: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Janssen, Eli Lilly, Galapagos, Gilead, Novartis, Pfizer, Sun Pharma, UCB Pharma, Speakers bureau: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Genentech, Janssen, Novartis, Pfizer, UCB Pharma, Atul Deodhar Grant/research support from: AbbVie, Eli Lilly, GSK, Novartis, Pfizer, UCB, Consultant of: AbbVie, Amgen, Boehringer Ingelheim, Bristol Myer Squibb (BMS), Eli Lilly, GSK, Janssen, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, Amgen, Boehringer Ingelheim, Bristol Myer Squibb (BMS), Eli Lilly, GSK, Janssen, Novartis, Pfizer, UCB, Proton Rahman Grant/research support from: Janssen and Novartis, Consultant of: Abbott, AbbVie, Amgen, BMS, Celgene, Lilly, Janssen, Novartis, and Pfizer., Speakers bureau: Abbott, AbbVie, Amgen, BMS, Celgene, Lilly, Janssen, Novartis, Pfizer, Helena Marzo-Ortega Grant/research support from: Janssen, Novartis, Consultant of: Abbvie, Celgene, Eli Lilly, Janssen, Novartis, Pfizer, UCB, Speakers bureau: Abbvie, Celgene, Eli Lilly, Janssen, Novartis, Pfizer, Takeda, UCB, Vibeke Strand Consultant of: AbbVie, Amgen, Biogen, Celltrion, Consortium of Rheumatology Researchers of North America, Crescendo Bioscience, Eli Lilly, Genentech/Roche, GlaxoSmithKline, Hospira, Janssen, Merck, Novartis, Pfizer, Regeneron Pharmaceuticals, Inc., Sanofi, UCB, Theresa Hunter Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, David Adams Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, David Sandoval Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Andris Kronbergs Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Baojin Zhu Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Ann Leung: None declared, Soyi Liu Leage Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Victoria Navarro-Compán Consultant of: Abbvie, Lilly, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, MSD, Lilly, Novartis, Pfizer, UCB